Exogenous Application of Biostimulants and Synthetic Growth Promoters Improved the Productivity and Grain Quality of Quinoa Linked with Enhanced Photosynthetic Pigments and Metabolomics - Nabila Rashid (MDPI AG, 2021)
Modern agriculture is mainly concerned with maximum resource use efficiency linked with greater productivity to feed the growing global population. The exogenous application of biostimulants is considered a sustainable approach to improve the growth and productivity of field crops. The present study was carried out to explore the comparative impact of biostimulants and synthetic compounds on quinoa crop (cultivar UAF-Q7), as it has gained significant popularity among agricultural scientists and farmers throughout the world, due to its high nutritional profile. A two-year field experiment was carried out at the Research Area of Directorate of Farms, University of Agriculture, Faisalabad, Pakistan. Application of moringa leaf extract (MLE) produced the maximum total chlorophyll (5.11 mg g−1) and carotenoids (1.2 mg g−1), compared with the control. Antioxidants’ activities and gas exchange attributes were also recorded as the highest following MLE application. Mineral elements in root and in shoot were found highest in response to MLE application. Similarly, application of MLE significantly improved the growth and yield attributes of quinoa. Mineral elements of grain (Mg, Zn and Fe) were also significantly enhanced. MLE was found to be more responsive in improving the growth and quality compared with synthetic compounds.